2005
DOI: 10.1002/asna.200510426
|View full text |Cite
|
Sign up to set email alerts
|

Global oscillations of a fluid torus as a modulation mechanism for black‐hole high‐frequency QPOs

Abstract: Abstract. We study strong-gravity effects on modulation of radiation emerging from accreting compact objects as a possible mechanism for flux modulation in QPOs. We construct a toy model of an oscillating torus in the slender approximation assuming thermal bremsstrahlung for the intrinsic emissivity of the medium and we compute observed (predicted) radiation signal including contribution of indirect (higher-order) images and caustics in the Schwarzschild spacetime. We show that the simplest oscillation mode in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…However, it was shown by a large scale ray tracing method that in this case, the X-ray luminosity is modulated by strong gravity effects (gravitational lensing and Doppler beaming) in photon propagation from oscillating disk to observer. It was found that the "observed" power in PDS Fourier spectra very strongly depends on lensing and beaming effects -for example, power in the vertical mode increases with inclination (Bursa 2005).…”
Section: Spectral States Qpo Modulation Of X-raysmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was shown by a large scale ray tracing method that in this case, the X-ray luminosity is modulated by strong gravity effects (gravitational lensing and Doppler beaming) in photon propagation from oscillating disk to observer. It was found that the "observed" power in PDS Fourier spectra very strongly depends on lensing and beaming effects -for example, power in the vertical mode increases with inclination (Bursa 2005).…”
Section: Spectral States Qpo Modulation Of X-raysmentioning
confidence: 99%
“…Of course, QPO appearance may also be intrinsically influenced by different physical conditions of the flow in different spectral states. This we study by a direct ray tracing from Mami Machida's accretion flow MHD 3D simulations in Schwarzschild spacetime (Bursa 2005).…”
Section: Spectral States Qpo Modulation Of X-raysmentioning
confidence: 99%
“…Since the oscillation epicyclic frequencies are strongly related with the black hole spin and mass, the instabilities and QPOs could be used to constrain the black hole properties [1,3,4]. On the other hand, we might also deduce the properties of the strong general relativistic region and it will give an opportunity to compare the various theories of the gravity [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…These models include non-geodesic effects in the accretion physics originating from the pressure forces by modelling the accretion flow in terms of a slightly non-slender pressure-supported perfect fluid torus[50,87,88]. There exist two main variants of non-axisymmetric disk-oscillation models: the first (denoted by NADO1 or Vertical Precession Resonance Model[84][85][86]) considers resonance between the vertical epicyclic frequency (f 1 = ν θ ) with m = −1 non-axisymmetric radial epicyclic frequency (f 2 = ν φ − ν r ) while the second (denoted by NADO2) assumes coupling between the m = −2 non-axisymmetric vertical epicyclic frequency (f 1 = 2ν φ − ν θ )[48][49][50] with the m = −1 nonaxisymmetric radial epicyclic frequency (f 2 = ν φ − ν r ). Here m refers to the azimuthal wave number of the non-axisymmetric perturbation.…”
mentioning
confidence: 99%